Signifying the relationship between counterproductive work behavior and firm's performance: the mediating role of organizational culture. Issue 6 (17th March 2021) - Abdullah, Muhammad Ibrahim; Huang, Dechun; Sarfraz, Muddassar; Naseer, Junaid; Sadiq, Muhammad Waqas
Abstract : Purpose: Organizations are facing several challenges in the current challenging business environment. The current study explores how counterproductive work behavior (CWB) affects bio-medical companies' firm performance in Pakistan. The study considers the mediating role of organizational culture and its impact on CWB and a firm's performance. Design/methodology/approach: Data were collected through a self-administered questionnaire. For data collection, 300 questionnaires were distributed among employees working in biomedical companies. Statistical analysis such as descriptive statistics, Pearson moment correlation and structural equation modeling (SEM) techniques was used to analyze the study variable's relationship and its effect on the firm's performance. Findings: The study results revealed that CWB and organizational culture significantly influence firm performance directly and indirectly. Moreover, organizational culture partially mediates the relationship between CWB and companies' performance. Originality/value: The current study plays a significant role in the firm's policy directions. There are limited research and information accessible to biomedical firms in Pakistan. Counterproductive job habits wind up becoming something that significantly affects the firm performance. This research adds to human resource management, corporate management and the business strategy literature.